ANALYSIS OF SERVICE QUALITY ON CUSTOMER SATISFACTION ON MUDHARABAH SAVING PRODUCTS - Nurochani, Nila; Amirullah, Mulia (Al-Infaq: Jurnal Ekonomi Islam, 2023)
This study aims to determine the level of customer interest and the level of company performance, and customer satisfaction with mudharabah savings products at Bank Syariah Indonesia in Tasikmalaya City. Importance Performance Analysis (IPA) determines the level of importance and implementation of mudharabah savings products. At the same time, they are calculating customer satisfaction using the customer satisfaction index (CSI). At the level of customer interest, it is found that the attributes of Islamic fund management and the security of funds are considered the most important, with an average value of 4.27. As for the performance level of the company's Islamic fund management attributes, the performance is regarded as the highest, with an average value of 3.83. Characteristics for the results obtained by customers in this study are considered unable to meet customer expectations, indicating its position in quadrant A (the top priority for repair). The calculation results show that customers/respondents are satisfied with the company's performance, with a CSI value of 70.93%.